Theorising the Public Sphere - Almuqren, Abdullah (Advances in Social Sciences Research Journal, 2024)
This paper examines the criticism of Jürgen Habermas’s idea of the public sphere, which is essential for sociology to comprehend the possibility for consensus in the communication processes of modern society. The main objective of this paper is to examine the evolution of the notion of the public sphere. This will be achieved by investigating the traditional concept of the public sphere and scrutinising its mechanisms. The public sphere is crucial in providing a platform for thoughtful discussions that strive to involve society in the process of constructing society itself. Undoubtedly, the evolution of social interactions in contemporary times is influenced by the standard possibilities and limitations imposed by public discussions. Amidst the era of digital advancements, the discussion around the public sphere has gained significant significance and complexity. Given the abundance and variety of public areas. This paper aims to elucidate the evolution of the traditional notion of the public sphere and analyse its defining features.